Analytical review of maintenance criteria for green roof in Malaysia / Shafikah Saharuddin, Natasha Khalil and Alia Abdullah Salleh - Shafikah, Saharuddin; Natasha, Khalil; Alia, Abdullah Salleh (Universiti Teknologi MARA, Perak, 2017)
The implementation of green roof on top of buildingsis becoming a trend in the urban cities and provides numerous benefits to the green development growth. Despite the benefit and enhancement on green roof installation, maintenance consideration isstill largely unexplored asthe main significant factor in the viability of green roof installation. This paper is aimed to identify the significant criteria of green roof maintenance practice in Malaysia. The literature findings revealed that there are generally twenty (20) criteria pointed as maintenance criteria. Out of 20, six maintenance criteria were identified as the most significant factors towards the best practice of green roof maintenance.